Research progress on the neural circuits mechanisms of anxiety - Gong, Wenxuan (Frontiers in Neural Circuits, 2025)
Anxiety disorders, as a critical mental health issue, profoundly impact an individual’s quality of life and social participation while imposing a considerable economic burden on communities. This underlines the urgent need for in-depth studies on the mechanisms underlying anxiety-like behaviors. These mechanisms are overseen by intricate neural regulatory networks, and the understanding of them has significantly advanced in recent decades, largely due to breakthroughs in neuroscience. Traditionally, research on brain regions controlling anxiety responses has been focused on key brain regions. However, recent studies have expanded this scope to encompass a broader network, including the amygdala, the bed nucleus of the stria terminalis (BNST), and the lateral habenula (LHb). Each of these regions plays a distinct role in mediating specific components of anxiety-like behaviors: the amygdala is central to emotional processing, the BNST contributes to the prolonged state of anxiety, and the LHb is pivotal in encoding negative signals that amplify aversive emotions. This review underscores the evolving and interconnected nature of these neural circuits, illustrating the intricate interplay in shaping anxiety-like behaviors. By proposing a layered representation of the neural circuitry, this study aims to unravel the neurobiological basis of anxiety-like behaviors, paving the way for more effective therapeutic strategies. These insights hold promise for advancing treatment approaches that could alleviate the burden of anxiety disorders in the future.